Alexandre Kojève and Carl Schmitt: the Political, Theology and the End of History - Jokubaitis, Linas (Politologija, 2023)
The aim of the article is to demonstrate that Carl Schmitt’s and Alexandre Kojève’s ideas about the political and the end of history have to be seen in the light of their theological presuppositions. The article defends the position that Schmitt’s The Concept of the Political is based on attempts to look at the problems of political anthropology from theological perspective, in which the dogma of original sin plays a central role. Kojève’s anthropotheistic system presents an inversion of this perspective, his ideas about the end of politics and history are inseparable from attempts to reduce theology to anthropology. His atheistic system of immanence provides a confirmation of Schmitt’s idea that the disappearance of the political is incompatible with the dogma of original sin. Kojève’s notion of the end of history and his concept of universal homogeneous state are formed by attempts to look at the concept of the political ex negativo. For Schmitt Christian theology provides a guarantee that the world will not be depoliticized, that enmity between humans will not be overome. French philosopher’s political theory is based on the idea that the end of history and the disappearance of the political would mark the actualisation of secularized Christian teaching. Kojève’s revised ideas about the destiny of humanity at the end of history, his position that humanity will return to animality, have to be understood in the context of his discussions with Schmitt.
Keywords: the political; original sin; anthropology; theology; antropotheism; end of history; universal homogeneous state